Agrodem : An Open-Source Model that Quantifies the Electricity Requirements of Irrigation - Korkovelos, Alexandros (World Bank, Washington, DC, 2022)
Sustainable Development Goal 7 (SDG 7) aims to ensure access to modern energy for all by 2030. Reaching the goal depends on ramping up electrification efforts. Most of the geospatial models developed to date to identify priority areas for energy access efforts focus on the electrification of households, giving short shrift to industrial and agricultural activities. But loads from those activities can be substantial. When combined with residential loads, they can affect the least-cost technology